Vulnerabilidade em saúde nos municípios do Ceará - Sousa, Gerlânia Maria Rocha (2021)
Health plays an important role in promoting sustainable development and reducing social vulnerability, being largely determined by environmental, economic and social factors. This thesis had as general objective to evaluate the health vulnerability conditions of the Ceará municipalities, through the application of a measurement instrument that allows to identify the determinants. It was proposed to build a Health Vulnerability Index (IVS) and to identify the dimensions that make up this vulnerability. To characterize the municipalities in relation to dimensions, factor analysis and grouping or cluster analysis were used. Through these multivariate analysis techniques, the IVS was calculated, so that it was possible to obtain the hierarchy of the municipalities of Ceará in relation to the studied vulnerability. To complement the study, the Pearson correlation coefficient was also adopted to analyze the correlation between the IVS and the variables that make up the dimensions of health vulnerability of the municipalities and the Moran Global and Local indices were calculated, in which the was able to visualize the spatial autocorrelation of the IVS regarding the municipalities in the state, verifying whether these locations are similar or not to their respective close neighbors. Data were obtained from the SUS IT Department (DATASUS), the Ceará Institute for Research and Economic Strategy (IPECE) and the Brazilian Institute of Geography and Statistics (IBGE), operated through the SPSS 23.0 and GeoDa programs. Through the application of factor analysis, six factors were obtained: indicator of financial resources and access to health care (Factor 1); indicator of socioeconomic characteristics (Factor 2); primary health care indicator (Factor 3); immunizations indicator (Factor 4); indicator of hospitalizations and deaths (Factor 5); and indicator of poor access to water and sanitation (Factor 6). Regarding the IVS, the results indicated that most municipalities in Ceará fall into the high health vulnerability range and a minority belong to the medium and low IVS groups. The cities in the interior and further away from the capital are those with the highest rate, bringing to light the reality present in many locations in Brazil. The study also showed that the dimensions that make up Factors 1, 2 3 are mostly more strongly and significantly correlated with the IVS. Finally, the spatial autocorrelation analysis showed that the high IVS regime stood out among the cities in the state, forming high-high agglomerations, thus confirming that the high vulnerability in these locations is related to the high vulnerabilities of the respective neighbors.